Flag day [videorecording (DVD)] - Penn, Sean, 1960-; Penn, Dylan; King, Regina; Winnick, Katheryn (Voco Productions, 2021)
Jennifer Vogel's father John taught her so much about love and joy, but he also happened to be the most notorious counterfeiter in US history. Directed by Sean Penn, the film stars Penn and his daughter Dylan Penn in an intimate family portrait of a young woman who struggles to rise above the wreckage of her past while reconciling the inescapable bond between a daughter and her father.